12. The Visual Art from Iasi between Tradition and Innovation - Ştefănescu Mirela (Sciendo, 2017)
After December 1989 in visual art from Iasi were produced numerous changes which have contributed to a new approach of the artistic phenomenon. That was the moment when a new generation of artists appeared and who, unshackle by the rigors of the communist regime, they have created artworks by experimenting the most varied ways of visual expression. An important aspect of this transition period is the place which visual art has it in the culture from Iasi and the aesthetic trends learned by the new generation alongside older artistic directions define the value of the contemporary cultural heritage from Iasi. Also, an important role in the presentation of the visual art from Iasi is the artistic education, which it‟s in a constant development with the advent of new specializations within the Faculty of Visual Arts and Design, highlighting the artistic and scientific potential of the professors and the students of "George Enescu" Național University of Arts from Iasi.